2015
DOI: 10.1016/j.schres.2014.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for reduced auditory lateral suppression in schizophrenia

Abstract: Background Well-documented auditory processing deficits such as impaired frequency discrimination and reduced suppression of auditory brain responses in schizophrenia (SZ) may contribute to abnormal auditory functioning in everyday life. Lateral suppression of non-stimulated neurons by stimulated neurons has not been extensively assessed in SZ and likely plays an important role in precise encoding of sounds. Therefore, this study evaluated whether lateral suppression of activity in auditory cortex is impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…CAPD frequently is diagnosed in children and adults presenting other comorbid or primary diagnoses, including peripheral hearing loss (Khavarghazalani et al, 2016), confirmed CANS deficits (e.g., multiple sclerosis- Musiek et al, 2005;Musiek & Weihing, 2011), traumatic brain injury (Saunders et al, 2015;Gallun et al, 2012), cerebrovascular accidents (e.g., Stroke-Koohi et al, 2016), psychiatric conditions (e.g., schizophrenia -Iliadou & Iakovides, 2003;Iliadou et al, 2013;Ramage et al, 2015;), cognitive deficits (e.g., Alzheimer's disease- Quaranta et al, 2015;Griffiths et al, 2012), and developmental disorders (e.g., attention deficit hyperactivity disorder [ADHD], dyslexia, language disorder). Sharma et al (2009) reported comorbidity of CAPD, language impairment, and reading disorders in 47% of a sample of school-age children (7-12 years) diagnosed with CAPD.…”
Section: Chermakmentioning
confidence: 99%
“…CAPD frequently is diagnosed in children and adults presenting other comorbid or primary diagnoses, including peripheral hearing loss (Khavarghazalani et al, 2016), confirmed CANS deficits (e.g., multiple sclerosis- Musiek et al, 2005;Musiek & Weihing, 2011), traumatic brain injury (Saunders et al, 2015;Gallun et al, 2012), cerebrovascular accidents (e.g., Stroke-Koohi et al, 2016), psychiatric conditions (e.g., schizophrenia -Iliadou & Iakovides, 2003;Iliadou et al, 2013;Ramage et al, 2015;), cognitive deficits (e.g., Alzheimer's disease- Quaranta et al, 2015;Griffiths et al, 2012), and developmental disorders (e.g., attention deficit hyperactivity disorder [ADHD], dyslexia, language disorder). Sharma et al (2009) reported comorbidity of CAPD, language impairment, and reading disorders in 47% of a sample of school-age children (7-12 years) diagnosed with CAPD.…”
Section: Chermakmentioning
confidence: 99%
“…On the basis of these models, a reduced GABA concentration may induce reduced mutual inhibition, and the dysfunction of mutual inhibition leads to less discrimination of received stimuli and longer processing time for the winning percept to build up. There is a study showing that individuals with schizophrenia have less lateral inhibition 19 . Our findings of the smaller number of verbal transformations with higher AQ or SPQ scores also indicate that these participants are poor at exploiting sequential information outside the focus of attention.…”
Section: Discussionmentioning
confidence: 99%